2019
DOI: 10.3390/cancers11070985
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib with Transarterial Chemoembolization Achieves Improved Survival vs. Sorafenib Alone in Advanced Hepatocellular Carcinoma: A Nationwide Population-Based Cohort Study

Abstract: We hypothesized that sorafenib plus transarterial chemoembolization (TACE) would confer survival benefits over sorafenib alone for advanced hepatocellular carcinoma (aHCC). We investigated this while using the population-based All-Cancer Dataset to assemble a cohort (n = 3674; median age, 60; 83% men) of patients receiving sorafenib for aHCC (Child-Pugh A) with macro-vascular invasion or nodal/distant metastases. The patients were classified into the sorafenib-TACE group (n = 426) or the propensity score-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 38 publications
5
31
2
Order By: Relevance
“…Our result, that the OS of patients with advanced HCC treated with combination therapy was superior to that of those patients treated with sorafenib alone, maps to the conclusions of 4 retrospective studies [19,31,56,57] but is in contrast to a clinical trial by Zhang and colleagues in 2015 [43]. In this study, despite a numerically greater median OS in the combined-therapy group than in the sorafenib-alone group (7.3 months vs. 6.0 months), no difference was observed between the two groups (P = 0.924).…”
Section: Discussionsupporting
confidence: 85%
“…Our result, that the OS of patients with advanced HCC treated with combination therapy was superior to that of those patients treated with sorafenib alone, maps to the conclusions of 4 retrospective studies [19,31,56,57] but is in contrast to a clinical trial by Zhang and colleagues in 2015 [43]. In this study, despite a numerically greater median OS in the combined-therapy group than in the sorafenib-alone group (7.3 months vs. 6.0 months), no difference was observed between the two groups (P = 0.924).…”
Section: Discussionsupporting
confidence: 85%
“…Although the results of sorafenib combined with TACE in the treatment of advanced HCC were not satisfactory, the combination of apatinib with TACE may provide a new method of combination therapy. Several retrospective studies compared sorafenib combined with TACE versus sorafenib alone for advanced HCC and found that combination therapy improved the patients' survival [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent phase III clinical trial showed that the addition of TACE to sorafenib failed to achieve significant survival benefit [6]. The reported median OS in sorafenib plus TACE group ranged between 12.8 and 17.3 months [6,[14][15][16]. In contrast, although the combination of apatinib with TACE was compared with TACE alone, the median OS of the combined treatment group was reported to be 11.9-22 months [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although technology was improved thereby promoting the development of HCC therapy, the treatment outcomes of HCC with PVTT remains poor, as expected. Currently, sorafenib or lenvatinib, transarterial chemoembolization (TACE), TACE plus sorafenib, percutaneous radiofrequency ablation (RFA), and radiotherapy, among others, are used in the clinical treatment of PVTT, but these treatment options remain unsatisfactory (8)(9)(10). Therefore, further research is urgently needed to investigate the optimal therapeutic strategy for HCC with PVTT.…”
Section: Introductionmentioning
confidence: 99%